Numerical study on compressive mechanical characteristics of filled jointed rock under confining pressure based on PFC - Song, Lang; Chai, Shaobo; Li, Jing; Song, Boyang; Chai, Lianzeng (Frontiers in Ecology and Evolution, 2023)
Confining pressure is an important factor affecting the strength and deformation characteristics of rock mass, it is of great significance to study the mechanical and deformation characteristics of jointed rock mass under confining pressure for the construction of deep underground engineering and the prevention of geological disasters. In order to study the mechanical and deformation characteristics of filled jointed rock under confining pressure, based on the laboratory experiment results of static uniaxial compression of filled jointed rock samples, the Particle Flow Code is used to conduct the numerical simulation. The strength characteristics, failure characteristics and micro-cracks development characteristics of filled jointed rock under different confining pressure levels, different joint inclination angles and different sample sizes are analyzed. The results show that the peak stress and peak strain increase with the increase of confining pressure level, and there is a strong linear relationship between peak stress and confining pressure level. The peak stress and initiation stress decrease first and then increase with the increase of joint inclination angle. With the increase of confining pressure level, the change law of initiation stress of filled jointed rock under different joint inclination angles is different. The confining pressure will prolong the development process of micro-cracks in filled jointed rock, which will make the distribution of micro-cracks more dispersed and the total number of micro-cracks increase. The failure mode changes from splitting failure to shear failure with the increase of confining pressure level. The change of joint inclination angle will seriously affect the failure mode and micro-cracks development characteristics of filled jointed rock.